Catalytic Production of Oxygenated and Hydrocarbon Chemicals From Cellulose Hydrogenolysis in Aqueous Phase - Xin, Haosheng; Hu, Xiaohong; Cai, Chiliu; Wang, Haiyong; Zhu, Changhui; Li, Song; Xiu, Zhongxun; Zhang, Xinghua; Liu, Qiying; Ma, Longlong (Frontiers in Chemistry, 2020)
As the most abundance of polysaccharide in lignocellulosic biomass--a clean and renewable carbon resource, cellulose shows huge capacity and roused much attention on the methodologies of its conversion to downstream products, mainly including platform chemicals and fuel additives. Without appropriate treatments in the processes of cellulose decompose, there are some byproducts that may be not chemically valuable or even truly harmful. Therefore, higher selectivity, more economical and greener processes would be favored and serve as criteria in correlational study. Aqueous-phase, an economically accessible and immensely potential reaction system, has been widely studied in the preparation of downstream products of cellulose. Accordingly, this mini-review aims at making a related summary about several conversion pathways of cellulose to target products in aqueous-phase. Mainly, there are four categories about the conversion of cellulose and down-stream products in the following: (i) cellulose hydrolysis hydrogenation to saccharides and sugar alcohols, like glucose, sorbitol, mannose, etc. (ii) selective hydrogenolysis leads to the cleavage of the corresponding glucose C-C and C-O bond, like ethylene glycol (EG), 1,2-Propylene glycol (PG), etc. (iii) dehydration of fructose and further oxidation, like 5-hydroxymethylfurfural (HMF), 2,5-furandicarboxylic acid (FDCA), etc. (iv) production of liquid alkanes via hydrogenolysis and hydrodeoxygenation, like pentane, hexane, etc. The representative products were enumerated, and the mechanism and pathway of mentioned reaction are also summarized in a brief description. Ultimately, the remaining challenges and possible further research objects are proposed in perspective to provide researchers with a lucid research direction.